2022
DOI: 10.3390/brainsci12010096
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intraoperative Hypothermia on Postoperative Cognitive Function in the Rat Hippocampus and Its Possible Mechanisms

Abstract: Intraoperative hypothermia is a common complication during operations and is associated with several adverse events. Postoperative cognitive dysfunction (POCD) and its adverse consequences have drawn increasing attention in recent years. There are currently no relevant studies investigating the correlation between intraoperative hypothermia and POCD. The aim of this study was to assess the effects of intraoperative hypothermia on postoperative cognitive function in rats undergoing exploratory laparotomies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…In other words, the precise protective mechanisms are not yet fully understood. As for our study, the memory decline was observed after the inadvertent intraoperative hypothermia both in clinical practice and animal experiment [ 4 , 42 , 45 , 46 ]. In regard to cerebral blood flow, the therapeutic hypothermia also induced reduction in post-ischemic hyperperfusion and sustained hypoperfusion [ 72 ].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In other words, the precise protective mechanisms are not yet fully understood. As for our study, the memory decline was observed after the inadvertent intraoperative hypothermia both in clinical practice and animal experiment [ 4 , 42 , 45 , 46 ]. In regard to cerebral blood flow, the therapeutic hypothermia also induced reduction in post-ischemic hyperperfusion and sustained hypoperfusion [ 72 ].…”
Section: Discussionmentioning
confidence: 81%
“…Clinical investigations and rat maze experiments both demonstrated that intraoperative hypothermia could lead to memory decline [ 4 , 42 ]. As memory is generated in the hippocampus, intraoperative hypothermia may negatively impact the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previously mentioned study, animals regained a normal core body temperature after 90 min after the 15 min forced swim in 24 ± 1°C cold water [ 16 ]. The physical consequences of hypothermia should not be overlooked: Several studies showed detrimental effects of hypothermia on spatial working memory and damage in the hippocampus [ 42 , 43 ]. A possible refinement of the forced swim test might therefore be using warmer water to prevent hypothermia, which is only rarely done so far [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MWM test is a reliable test correlated with hippocampal synaptic plasticity (Vorhees & Williams, 2006). Studies have shown that intraoperative .96 e,a,c,h,j 0.15 6 14 37.56 f,a,c,d,e,g,h,i,j 0.52 7 14 37.63 g,a,c,d,e,f,g,i,j 0.11 8 14 37.61 h,a,cd,e,f,g,i,j 0.18 9 14 37.52 i,a,d,f,g,h 0.12 10 14 37.84 j,a,c,e,f,g,h 0.17 hypothermia negatively affects spatial memory (Xu et al, 2022). The hippocampus is a brain region that is responsible for spatial memory functions (Bellmund et al, 2018) and is quite responsive to stress (Eichenbaum, 2000;O'Keefe & Nadel, 1979;Scoville & Milner, 1957).…”
Section: Discussionmentioning
confidence: 99%